Determination of the Risk of Caries Origin in Early Childhood - V. Merglová (Czech Dental Chamber, 2007)
Caries is presently considered as an infection disease, which requires new preventive and therapeutic procedures. Attention is drawn to early detection and evaluation of protective and risk factors from the standpoint of caries origin and the determination of the risk of caries origin already in the pregnant woman or the first visit of the child to the dentist. The first stomatological examination of the child should be done at 12 months of age at the latest and, based on the determination of the risk, to plan most suitable preventive measures, which could eliminate the risk of the origin of sc. caries in early childhood, but also the frequency of visits of the child to the dentist. In children at a high risk of caries, control examinations in three month intervals are recommended and should be associated with administration of fluoride varnish, whereas in children at the low risk two visits to the dentist should be sufficient and the varnish is not necessary to apply.